PENGARUH KEJELASAN SASARAN ANGGARAN DAN PARTISIPASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH KOTA MANADO - Nangoy, Nikita Angelita Maria; Sondakh, Jullie J.; Sabijono, Harijanto (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Indonesian Law Number 46 of 2011 on Civil Servant Performance Appraisal will help develop effectivity and efficiency of employee performances to reach the objection and vision and mission of a regional administration.The purpose of this study was to determine whether the clarity of budge targeting and budget participation has effect by partial and by simultaneous on the performance of the government officials. The hypothesis was tested using t test and then f test. The population number in this study is 441 people. And, the samples were 30 people of lower managers and staffs in financial and reporting department. The research method used questionnaire with Likert scale measurement. The analytical method used in this research was multiple regression analysis in which the process of data analysis was performed with the aid of computer technology SPSS version 22. The results of the analysis by the t test states that the clarity of budget targeting variables X1 = is 0.317> 0.005, it means that H0 is accepted and Ha rejected, which in other words the clarity of budget targeting does not affect the performance of government officials. Participation budget X2 = is 0.001 <0.005, this means that Ha is accepted and H0 is rejected, which in other words budget participation does affect the performance of government officials. The results of the analysis through F test shows that the level of significance of the variables X1 and X2 is 0.002 <0.005,this means that H0 is rejected and Ha accepted; in other words, X1 and X2 simultaneously have a significant effect on the performance of government officials (Y). Keywords: clarity of budget targeting, budget participation, performance of local government officials